Mekanisme Tata Kelola Korporasi sebagai Pereduksi Praktik Perekayasaan Laba - Alwan Sri Kustono (Jurnal Ekonomi Akuntansi dan Manajemen, 2018)
Management can choose accounting policies for expected earnings reporting. This study purpose to examineeffect of corporate governance mechanism managerial ownership, such as audit committees, board size, composition of independent commissioners, board size, and firm size. The sample used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2014-2015. Institutional investors, managerial ownership, audit committees, have a positive coefficient. This shows that the independent variable has a positive influence on earnings management that means earnings management changes in the direction of changes in the independent variables. The proportion of independent commissioners, board size, firm size has a negative coefficient. This shows that these independent variables has a negative influence on earnings management which means earnings management changes direction with changes in the independent variable. Keywords: Institutional investors, managerial ownership, audit committees, independent commissioners, board size, firm size, earnings management